Dismembered Bodies, Dismembered Texts: Supernatural Anthologies and the Re-animation of the Dead in Post-revolutionary France (1802-1822) (ENTHYMEMA, 2019)
The import of British Gothic novels in post-revolutionary France, from 1797 onwards, triggered French publisher to capitalize on the vogue of supernatural narratives. One of the results was the publication of a number of anthologies, hastily composed by cutting and pasting Old Regime collections, whose first example was the anonymous Le Livre des prodiges (1802). This essay reinstates the supernatural anthologies of 1802-1822 as a powerful link between the British Gothic and later French fantastic literature (particularly Alexandre Dumas), at the same time analysing how the very operation of cutting and pasting pre-revolutionary texts resonates with distinctly post-revolutionary anxieties.
Keywords: gothic; supernatural; phantasmagoria; Alexandre Dumas; French Revolution